Purinergic mechanosensory transduction and visceral pain - Burnstock Geoffrey (SAGE Publishing, 2009)
Abstract In this review, evidence is presented to support the hypothesis that mechanosensory transduction occurs in tubes and sacs and can initiate visceral pain. Experimental evidence for this mechanism in urinary bladder, ureter, gut, lung, uterus, tooth-pulp and tongue is reviewed. Potential therapeutic strategies are considered for the treatment of visceral pain in such conditions as renal colic, interstitial cystitis and inflammatory bowel disease by agents that interfere with mechanosensory transduction in the organs considered, including P2X3 and P2X2/3 receptor antagonists that are orally bioavailable and stable in vivo and agents that inhibit or enhance ATP release and breakdown.